Pengaruh Efikasi Diri Dan Pendidikan Terhadap Intensi Kewirausahaan Dengan Lingkungan Sosial Sebagai Variabel Moderasi - Andrew Bryan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to determine the effect of self efficacy and education on the intention of entrepreneurship with social environment as a moderation variable. Methods of data collection using questionnaires. The respondents of this research are students of Faculty of Economics University Tarumanagara. The study was conducted in May 2018. The method of data analysis using multiple regression with the moderation variable. The results of the study conclude that self efficacy and education have a positive effect on the intention of entrepreneurship. Social environment variables deserve to be a moderation variable because there is an effect of self efficacy and education on the intention of entrepreneurship moderated by social environment..